3D printing as novel tool for fruit-based functional food production. (October 2021) - Tomašević, Igor; Putnik, Predrag; Valjak, Filip; Pavlić, Branimir; Šojić, Branislav; Bebek Markovinović, Anica; Bursać Kovačević, Danijela
Graphical abstract: Highlights: The 3D printing (3DP) of food is innovative approach in functional food production. The major benefits of 3DP are product diversity, customization and personalization. 3DP fruit products can be enriched with functional ingredients from various origins. Legislation that regulates safety of 3D printing in the food sector is still missing. Abstract : Daily consumption of fruits/vegetables has a preventive effect against several chronic diseases, mainly because of their bioactive compounds (BACs) and potent antioxidant activity. As consumers demand more of the health-promoting products, it would be a great challenge to enrich these products with functional ingredients that they do not naturally possess, such as lipophilic BACs, probiotics, proteins/peptides, and so on. Currently, a great potential in the field of food innovation can be achieved through 3D food printing (3DP). This is a technique for producing three-dimensional food products of any shape and dimension, with preferred flavors, and desired nutritional compositions. 3DP could be a promising tool to incorporate sensitive and easily degradable BACs and other functional ingredients into functional 3DP food products, making a great contribution to healthy food production. Therefore, 3DP could contribute greatly to increasing the consumption of fruits and vegetables and promoting health. Other advantages of 3DP include time and energy savings, sustainability, and personalized, reproducible food production. However, the safety of 3DP foods has been less extensively addressed. Nevertheless, the use of innovative non-thermal technologies can extend the shelf-life and nutritional value of 3DP foods. In conclusion, the application of 3DP in food manufacturing could overcome major limitations of traditional manufacturing and provide solutions to the challenges of processing fruit-based functional foods.